The Effect of Target Shooting Training on the Results of Shooting Accuracy in Soccer Atletes - Arif Hidayat; Aprizal Fikri; Martinus Martinus; Muslimin Muslimin; Bayu Hardiyono (UNIB Press, 2024)
The aim of this research is to determine empirically the effectiveness and results of the footwork technique training model for badminton athletes aged 9-11 years. The research method used is research and development (R&D) with the Borg and Gall model. The data analysis technique uses the t test with SPSS software to test effectiveness. The effectiveness test was carried out on athletes aged 9-11 years in Tasikmalaya. From the calculation results it is known that the pre-test average is 2.41 and the post-test average is 3.52. Thus, it can be concluded that the badminton footwork training model for athletes aged 9 - 11 years can be developed and implemented and is effective in improving the accuracy of badminton footwork movements.